Advancing Teacher Evaluation: E-Portfolio Development - Iskandar, Didik; Hasani, Aceng; Hidayatullah, Hidayatullah (Universitas Islam Negeri Raden Intan Lampung, 2024)
E-portfolios are increasingly common in developed countries, with over half of colleges and universities offering e-portfolio-based learning. This study aims to enhance the quality of education in vocational high schools (SMK) in Tangerang district by using e-portfolio-based assessments to evaluate and improve teacher performance. The result is an e-portfolio assessment instrument, accessible via a website, for both teachers and students. The development model employed is the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). Tools used in this study include validation sheets, project scores, and response questionnaires. Based on expert and user validations, the assessment instrument received a score of 86.00%, categorizing it as 'very valid'. The reliability analysis showed an average reliability coefficient of 0.783, which is considered high. To improve the quality of education in vocational high schools (SMK) in Tangerang Regency, it is recommended to use e-portfolios to evaluate and improve teacher performance. The inputs and indicators for developing teacher performance should be managed by an application that is user-friendly and comprehensive, covering everything from activities to evaluations. Therefore, the e-portfolio application was created to enhance teacher performance and facilitate the evaluation process.